Phosphoproteomic analyses reveal novel cross‐modulation mechanisms between two signaling pathways in yeast. Issue 12 (9th December 2014) - Vaga, Stefania; Bernardo‐Faura, Marti; Cokelaer, Thomas; Maiolica, Alessio; Barnes, Christopher A; Gillet, Ludovic C; Hegemann, Björn; van Drogen, Frank; Sharifian, Hoda; Klipp, Edda; Peter, Matthias; Saez‐Rodriguez, Julio; et al.
Abstract Cells respond to environmental stimuli via specialized signaling pathways. Concurrent stimuli trigger multiple pathways that integrate information, predominantly via protein phosphorylation. Budding yeast responds to NaCl and pheromone via two mitogen‐activated protein kinase cascades, the high osmolarity, and the mating pathways, respectively. To investigate signal integration between these pathways, we quantified the time‐resolved phosphorylation site dynamics after pathway co‐stimulation. Using shotgun mass spectrometry, we quantified 2, 536 phosphopeptides across 36 conditions. Our data indicate that NaCl and pheromone affect phosphorylation events within both pathways, which thus affect each other at more levels than anticipated, allowing for information exchange and signal integration. We observed a pheromone‐induced down‐regulation of Hog1 phosphorylation due to Gpd1, Ste20, Ptp2, Pbs2, and Ptc1. Distinct Ste20 and Pbs2 phosphosites responded differently to the two stimuli, suggesting these proteins as key mediators of the information exchange. A set of logic models was then used to assess the role of measured phosphopeptides in the crosstalk. Our results show that the integration of the response to different stimuli requires complex interconnections between signaling pathways.